HUBUNGAN PARITAS IBU HAMIL DENGAN KEPATUHAN DALAM MELAKUKAN KUNJUNGAN ANTENATAL CARE DI WILAYAH KERJA PUSKESMAS PENANAE KOTA BIMA TAHUN 2025 - Bunga Uswatun Hasanah; Yati Purnama; Nur Islamyati (Akademi Kebidanan Harapan Bunda Bima, 2025)
Antenatal care (ANC) visits are an important effort to monitor the health of both mother and fetus, detect risks, and prevent pregnancy complications. However, the level of maternal compliance in attending ANC visits still varies. One of the factors influencing this compliance is parity; mothers with previous childbirth experience tend to have different perceptions and motivations regarding ANC examinations. This study aims to analyze the relationship between parity and ANC visit compliance in the working area of Penanae Health Center, Bima City, in 2025. This research employs a quantitative method with a correlational analytic approach and a cross-sectional design. The study population consists of all pregnant women in the Penanae Health Center working area, totaling 273 individuals, with a sample of 73 respondents determined using the Slovin formula and the simple random sampling technique. The research data are secondary data obtained from medical records. The independent variable is parity, while the dependent variable is ANC visit compliance. Data analysis was performed using the Chi-Square test with a significance level of p < 0.05. The results showed that most respondents were multiparous and the majority were compliant in attending ANC visits. The Chi-Square test produced a p-value of 0.008 (p < 0.05), indicating a significant relationship between parity and ANC compliance. It is concluded that primiparous mothers tend to be more compliant than multiparous or grand multiparous mothers.